Research Progress on Mitophagy in the Treatment of Ischemic Stroke - Yan, Yixiao; Li, Qiao; Zhang, Hang; Lu, Xiaohong (Journal of Contemporary Medical Practice, 2025)
Ischemic stroke is a leading cause of mortality and disability globally. Inadequate blood flow results in the deprivation of glucose and oxygen in brain cells, which disrupts cellular homeostasis and initiates a series of molecular reactions. These processes contribute to the accumulation of impaired mitochondria. As a selective type of autophagy, mitophagy plays a central role in mitochondrial quality control and is important for preserving mitochondrial integrity and function. It promotes neuronal survival and improves neuronal function by clearing depolarized mitochondria. Studies have indicated that mitophagy is closely associated with ischemic stroke. In this review, we discuss the mechanisms underlying mitophagy induction, the impact of stroke on mitophagy, and the role of mitophagy in ischemic brain tissue. We further highlight the activation of mitophagy as a potential therapeutic target for ischemic stroke.